2016
DOI: 10.1007/978-3-319-49304-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Gender-Neutral Digital Library Creation: A Case Study Using the GenderMag Toolkit

Abstract: Abstract. Software is assumed by its creators and maintainers to be gender-neu tral: that is, that it is equally well suited for use by any user, regardless of gender. We investigate this assumption in the digital libraries context through analysis of a significant digital library construction and maintenance tool-the Greenstone Digital Librarian Interface (GLI)-using the GenderMag toolkit. GenderMag provides personas whose approaches to software use fall across the spectrum of gender-stereotypic actions and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…GenderMag It is a software inspection method to solve gender biases in software developers' problem-solving experiences [SLR Burnett et al 2018)]. Previous research shows that GenderMag is very effective in identifying gender-inclusiveness issues when evaluating technologies [SLR Hill et al 2016;Vorvoreanu et al 2019;Burnett et al 2017)] and was found a powerful tool to uncover potential gender biases in system functionality and interface design [SLR (Cunningham et al 2016)].…”
Section: Tools Models and Theories To Foster Perceived Diversity-inclusiveness In Sementioning
confidence: 99%
“…GenderMag It is a software inspection method to solve gender biases in software developers' problem-solving experiences [SLR Burnett et al 2018)]. Previous research shows that GenderMag is very effective in identifying gender-inclusiveness issues when evaluating technologies [SLR Hill et al 2016;Vorvoreanu et al 2019;Burnett et al 2017)] and was found a powerful tool to uncover potential gender biases in system functionality and interface design [SLR (Cunningham et al 2016)].…”
Section: Tools Models and Theories To Foster Perceived Diversity-inclusiveness In Sementioning
confidence: 99%
“…Empirical studies have found GenderMag to be effective at identifying inclusivity bugs and at pointing toward effective fixes [12,14,22,35,61,69,80]. However, in the realm of CS education, the only work relating to GenderMag is Oleson et al 's Action Research investigation into how to teach GenderMag in face-to-face university CS classes [59].…”
Section: Background: Gendermag's Facets and Personasmentioning
confidence: 99%
“…Perhaps the most developed formalized method so far for considering gender in technology design is the GenderMag method [36,37,97]. It consists of a specialized cognitive walkthrough and a set of personas structured around five underlying gender differences in technology use (see Sections 2.4, 2.5, 2.6), offering HCI designers step-by-step how-to guides and ready-to-use forms to uncover and document gender barriers in existing systems [33,56,144,182]. Recent work has also shown its promise as a design aid [211] (Figure 4.1).…”
Section: Gender-inclusive Designmentioning
confidence: 99%